Augmentation of Rotator Cuff Repair With Soft Tissue Scaffolds. Issue 6 (10th June 2015) - Thangarajah, Tanujan; Pendegrass, Catherine J.; Shahbazi, Shirin; Lambert, Simon; Alexander, Susan; Blunn, Gordon W.
Background: Tears of the rotator cuff are one of the most common tendon disorders. Treatment often includes surgical repair, but the rate of failure to gain or maintain healing has been reported to be as high as 94%. This has been substantially attributed to the inadequate capacity of tendon to heal once damaged, particularly to bone at the enthesis. A number of strategies have been developed to improve tendon-bone healing, tendon-tendon healing, and tendon regeneration. Scaffolds have received considerable attention for replacement, reconstruction, or reinforcement of tendon defects but may not possess situation-specific or durable mechanical and biological characteristics. Purpose: To provide an overview of the biology of tendon-bone healing and the current scaffolds used to augment rotator cuff repairs. Study Design: Systematic review; Level of evidence, 4. Methods: A preliminary literature search of MEDLINE and Embase databases was performed using the terms rotator cuff scaffolds, rotator cuff augmentation, allografts for rotator cuff repair, xenografts for rotator cuff repair, and synthetic grafts for rotator cuff repair . Results: The search identified 438 unique articles. Of these, 214 articles were irrelevant to the topic and were therefore excluded. This left a total of 224 studies that were suitable for analysis. Conclusion: A number of novel biomaterials have been developed into biologically and mechanically favorable scaffolds. Few clinical trials have examined their effect on tendon-bone healing in well-designed, long-term follow-up studies with appropriate control groups. While there is still considerable work to be done before scaffolds are introduced into routine clinical practice, there does appear to be a clear indication for their use as an interpositional graft for large and massive retracted rotator cuff tears and when repairing a poor-quality degenerative tendon.